Look again : a memoir - Trembley, Elizabeth A. (Elizabeth Ann), 1963- (Street Noise Books, 2022)
Trauma can make truth hard to find. Have you ever experienced a terror, grief, or confusion so great that when you try to share it you can only find shattered images floating in darkness? You try over and over, but can't tell the story, to yourself or to anyone else. Look Again presents us with six variations of the same event, seen through the different lenses caused by other life revelations. It explores the fragmenting nature of trauma by tracing the convoluted evolution of the author's story, a process often experienced by trauma sufferers and their loved ones.